Development of e-module combining science process skills and dynamics motion material to increasing critical thinking skills and improve student learning motivation senior high school - Fengky Adie Perdana; Sarwanto Sarwanto; Sukarmin Sukarmin; Imam Sujadi (Universitas Sebelas Maret, 2017)
Learning media is one of the most components in the teaching and learning process. This research was conducted to design and develop the electronic modules combining science process skills and dynamics motion content for increasing critical thinking skills and improve student learning motivation for senior high school. The Methods used in this research is Research and Development (R&D). Model research and development using a research 4D Thiagarajan model. Physics module was developed using science process skills approach: observing, formulating the problem, formulating a hypothesis, identify variables, conduct experiments, analyse the data, summarise and communicate. The results showed that: 1) the electronics module has been developed by integrating the science process skills for enhancing critical thinking skills and student motivation. 2) Electronic Module Physics-based science process skills meet the criteria very well, judging from the results of validation content, validation media, validation of peer education and practitioners, with an average value of 3.80 is greater than the minimum eligibility 3.78. 3) effectiveness the modules of science process skills got N-gain value obtained from a large trial in grade samples of 0.67 and 0.59 in the control group were categorised as moderate. 4) Implementation of electronic modules Physics-based science process skills is considered an effective to enhance the students' motivation. Statistical analysis showed a significance value of 0.027 is lower than the significance level α = 0.05, this means that there are significant differences between learning motivation grade sample and the control class. As a result of analysis data obtained from the research, it was seen that the students' motivation that uses Physics module based science process skills better than conventional learning.